"In Storytelling, We See the Performance More from the Personality": The Goals and Self-Regulation on Storytellers of Other-Language - Gigih Widy Merbawani; Slamet Setiawan; Syafi’ul Anam (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Research on the Storytelling perspectives of the storyteller is not quite new, however, further discussion is done by seeking the educational implications of Storytelling used. Therefore, this study investigates the cases of three active storytellers under the learning community in students' activity at University. The findings suggest that the teacher candidates subjectively position themselves during the learning process of becoming a good storyteller in the Storytelling Community in three ways; (a) they positioned themselves as a storyteller through self-management and self-discipline in advancing their knowledge to be a good Storytelling Performer, (b) they engaged in professional interaction with the audience and other storytellers in community, (c) as the other storytellers inside the community capitalized on their simultaneous storytelling experience as a valuable resource in the storytelling-learning community